Structure-activity relationships of mixed σ1R/σ2R ligands with antiproliferative and anticancer effects. (1st November 2022) - Fallica, Antonino N.; Ciaffaglione, Valeria; Modica, Maria N.; Pittalà, Valeria; Salerno, Loredana; Amata, Emanuele; Marrazzo, Agostino; Romeo, Giuseppe; Intagliata, Sebastiano
Graphical abstract: Abstract: The overexpression of σ receptors (σRs) in various types of tumors has prompted a deep investigation of their role in cancer pathophysiology. Consequently, σR ligands have been widely studied in vitro and in vivo for their antiproliferative effects as a novel potential class of chemotherapeutic agents, both alone and in combination with other anticancer drugs. A growing body of evidence highlights that σR ligands can inhibit cancer cells' survival, migration, and proliferation, thanks to the modulation of a wide panel of tumorigenic pathways. In addition to their antitumor activity, σR ligands are gaining momentum as radiotracers for PET and SPECT imaging applications. The purpose of this review is to report on recent advances in the development of σR ligands. In particular, herein, we describe the structure–activity relationships of structurally diverse mixed σ1 R/σ2 R ligands that showed promising antitumor profiles towards a variety of cancer cell lines.